The adventures of Tintin : Red Rackham's treasure - Hergé (Little, Brown, 2008)
In volume 4, Tintin and his team continue their journey to explore the world and solve mysterious cases. From tracking down the tracks of a smuggling gang to exploring unique ancient tombs, Tintin is always willing to face dangers and challenges. The combination of action, mystery and fiction creates a dramatic and engaging experience for readers of all ages.